Duelling narratives of chironomids and pollen explain climate enigmas during The Last Glacial-Interglacial transition in North Island New Zealand. (1st July 2021) - Rees, Andrew B.H.; Holt, Katherine A.; Hinojosa, Jessica L.; Newnham, Rewi M.; Eaves, Shaun; Vandergoes, Marcus J.; Sessions, Alex L.; Wilmshurst, Janet M.
Abstract: The Last Glacial-Interglacial Transition (LGIT) was a dynamic stage of Earth's history, and the difficulty of reconstructing this complex interval may be compounded by divergent proxy records, often collected from the same archive. To overcome this obstacle, we exploit the contrasting biological preferences of chironomids to both summer temperature and degree days (positive) and pollen to both the length of the growing season (positive) and winter duration (negative), recorded by a small lake in the central North Island of New Zealand. The climate proxy records are anchored to shifting zonal boundaries (e.g., southern westerly wind belt) via the hydrogen isotope ratios of leaf wax n -alkanes (δDwax ). These results enable us to interrogate the structure of the LGIT and address two fundamental questions: 1) Is there evidence for Holocene-like temperatures during the early deglacial? and 2) Were early Holocene summers cool? Lake sediment δDwax values indicate a poleward retreat of the westerlies around 18, 000 calibrated years before present (cal kyr BP), signalling the onset of climate amelioration for the region. Remarkably, the independently derived summer and mean annual temperature reconstructions are anti-phased. Chironomid-inferred summer temperatures surpass modern values by 17.5 cal kyr BP, whereas pollen-inferred mean annual temperatures remain supressed. Summers cool from 17.5 to 11 cal kyr BP, when they reach a minimum for the record, while winter and mean annual temperatures simultaneously warm to a maximum. The chironomid record generally traces regional insolation, although an Antarctic template imprints on this trend with declining summer temperatures during the Antarctic Cold Reversal (ACR) and warming during the Younger Dryas (YD). Forest development during the early LGIT, on the other hand, is supressed by cool, dry winters, punctuated by severe frosts, despite being set against a backdrop of overall warming; the successional pattern is best explained by a latitudinal retreat of the westerlies. Our findings underscore the complementarity of multiple bioproxy responses and reveal the importance of seasonal heat and energy distribution during the LGIT. Highlights: We present deglacial temperature reconstructions from North Island New Zealand. Based on hydrogen isotope ratios of leaf wax n -alkanes, westerlies retreat poleward from 18 to 13 cal kyr BP. Chironomid-based summer temperatures reach modern values by 17 cal kyr BP and then decline to a minimum at 11 cal kyr BP. Pollen-based mean annual temperatures are conspicuously anti-phased to chironomid inferences. Chironomids respond to regional insolation while forest development follows latitudinal retreat of the westerlies.